WAYS TO IMPROVE THE EFFICIENCY OF USING FIXED ASSETS OF THE ENTERPRISE PJSC "PRYLUTSK BAKERY" - CHEREP, OLEKSANDR; PRYKHODKO, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Undoubtedly, at any enterprise to increase the volume of production requires the provision of fixed assets. Namely, such fixed assets, which consist of buildings, structures, machines, tools and other means of labor involved in the production process, are the most important basis of the enterprise. Therefore, the company must set itself the priority - it is rational and economical use of fixed assets. Regardless of the form of ownership, for any enterprise fixed assets are the technical and material basis for the production process. Many companies face the problem of efficient use of fixed assets, ie inefficient attitude to the use of fixed assets, use worn and obsolete equipment. This problem is very relevant today. The stages of the management mechanism for improving the efficiency of use of fixed assets at the production enterprise are studied. Stages of the control mechanism are characterized: formation, use, renewal, disposal at the production enterprise. Each stage of the mechanism of management of fixed assets of the enterprise is characterized. The company needs constant modernization, automation and mechanization of production, along with the efficient use of fixed assets, gives a greater opportunity to expand production at the enterprise. The technical improvement of means of labor is revealed, and how the employees of the enterprise should work and carry out their activity. Thus, for efficient production activities, it is necessary to provide fixed assets. The main ways to improve PJSC "Pryluky Bakery" are: technical re-equipment on the basis of integrated automation; replacement of obsolete equipment, modernization of equipment; introduction of scientific organization of labor and production; improving the provision of material and technical resources. It is the efficient use of fixed assets that allows to increase production and increase the return of the created production potential, at the same time to increase the profitability of products. Fixed assets are the main part of the material and technical base of the enterprise. Increasing the efficiency of means of labor, at the same time increases the economic potential of the enterprise, increases production capacity, which is the result of increased output. This problem must be solved quickly, because the irrational and inefficient use of fixed assets reduces the competitiveness and deteriorates the financial condition of the enterprise. It is necessary to involve specialists to carry out complex repairs, improve the level of specialization of production, upgrade equipment, while improving the composition and condition of fixed assets, improve and improve the organization of labor, then it will be efficient and cost-effective use of fixed assets.